Cost implications of patient spending on heart failure medications in the US Medicare program. Issue 2 (19th February 2021) - McGee, Blake Tyler; Parikh, Rishika; Phillips, Victoria
Abstract: Objectives: The aim of this study was to model the associations between patient spending on heart failure (HF) medications and Medicare and all-payer expenditures on health care services for participants in the Medicare prescription drug (Part D) program. Methods: Correlational analysis of pooled 2011–12 data from the Medicare Current Beneficiary Survey. Analysis was restricted to community-dwelling beneficiaries with self-reported HF at baseline, continuous Part D coverage, and no Low-Income Subsidy (LIS). The main predictor was mean patient expenditure on a HF-related prescription per 30-day supply. The outcomes were all-payer and Medicare-specific payments for inpatient and total health care services during the observation year. Key findings: Mean patient drug expenditure was not statistically associated with Medicare or all-payer inpatient payments or (after covariate adjustment) with total health care payments. However, patient expenditure was statistically associated with total Medicare payments, e γ = 1.022, 95% CI [1.004 to 1.041]. Marginal effects analysis predicted an average rise in total Medicare payments of $190.32, 95% CI [$40.54 to $341.10], for each additional $1 of patient spending per prescription, P = 0.013. Given an average 2.4 HF-indicated drug classes per participant and assuming 12.2 copays per year, a hypothetical $1 increase in prescription copay predicted a net loss to Medicare of $160.90 per participant. Conclusion: Prescription drug spending by Medicare beneficiaries with HF was not associated with higher inpatient or all-payer costs. A modest association between patient drug spending and total Medicare costs was observed, but longitudinal and cost-effectiveness analyses are needed to support causal inference.